1988
DOI: 10.1128/aac.32.1.128
|View full text |Cite
|
Sign up to set email alerts
|

Effect of protein binding on drug penetration into blister fluid

Abstract: The effect of protein binding on drug penetration into blister fluid was evaluated by using cefonicid, ceftizoxime, and cefotaxime. Drug concentrations in a chamber with a high surface area/volume ratio (i.e., paper disk) follow changes in serum more closely than do those in a chamber with a low surface area/volume ratio. Both the area under the concentration-time cu'rve ratio and the concentration ratio (by the disk method) for cefonicid were statistically lower than the ratios for ceftizoxime and cefotaxime.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
12
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 11 publications
(13 reference statements)
2
12
0
Order By: Relevance
“…Our findings confirm the results of previous studies using artificially created models with a high SA/V ratio (i.e., filter paper disk, cotton thread, and an in vitro kinetic model) which noted that drug concentrations in these fluid spaces tend to parallel changes in serum (3,6,(17)(18)(19). In contrast, drug concentrations in chamber models with a low SA/V ratio (i.e., blister fluid, tissue cage), which are not representative of a surgical wound, have delayed equilibrium, lower peak levels, and prolonged concentrations in comparison with serum (1,3,4,6,20).…”
supporting
confidence: 82%
“…Our findings confirm the results of previous studies using artificially created models with a high SA/V ratio (i.e., filter paper disk, cotton thread, and an in vitro kinetic model) which noted that drug concentrations in these fluid spaces tend to parallel changes in serum (3,6,(17)(18)(19). In contrast, drug concentrations in chamber models with a low SA/V ratio (i.e., blister fluid, tissue cage), which are not representative of a surgical wound, have delayed equilibrium, lower peak levels, and prolonged concentrations in comparison with serum (1,3,4,6,20).…”
supporting
confidence: 82%
“…Since several blisters are formed with either of these procedures, multiple samples can be obtained by emptying the contents of individual blisters with a sterile needle and syringe at appropriate sampling times. Fluid present in the inflammatory blisters contains a higher protein content than does ECF, so the antibiotic concentration appears higher than that present in true ECF for protein-bound drugs (88,104).…”
mentioning
confidence: 99%
“…Studies in animals (6,19,20), in vitro models (21), and humans (16,22,25) have shown that high serum protein binding significantly affects the kinetics of extravascular drug distribution. High binding to serum proteins (e.g., albumin) in the intravascular space tends to reduce the amount of drug available for diffusion into extravascular spaces (22,25).…”
mentioning
confidence: 99%
“…A 10-fold-higher dose of dicloxacillin was also studied to determine the effect of drug concentration on Studies in animals (6,19,20), in vitro models (21), and humans (16,22,25) have shown that high serum protein binding significantly affects the kinetics of extravascular drug distribution. High binding to serum proteins (e.g., albumin) in the intravascular space tends to reduce the amount of drug available for diffusion into extravascular spaces (22,25). However, a considerable amount of serum protein also is distributed to the extravascular space; for example, approximately 60% of the total exchangeable albumin in the body is found in the extravascular space, but at lower concentrations than in the intravascular space (17).…”
mentioning
confidence: 99%